The Influence Of Village Funds And Capital Expenditures On Village Development Performance In Morowali District - Afrainti, Indah; Din , Muhammad (ADPEBI, 2024)
Village development is seen as an integral part of national development with the principle of regional autonomy as the first step to achieving higher national economic growth, so as to improve the quality of life of people in the regions. Improving the quality of life of village communities is the main focus in village development efforts. This research has two main objectives, namely: 1) Identifying the impact of Village Funds on the level of village development as measured through IDM. 2) Analyze the effect of Capital Expenditures on the level of village development as measured using IDM. This research is quantitative and uses secondary data. This research uses the Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis technique with the help of the WarpPls 7.0 program to collect samples. The sampling technique used the census method to obtain a total sample of 126 villages in Morowali Regency. The research results show that: 1) IDM is positively and significantly influenced by the Village Fund. 2) IDM is positively and significantly influenced by Capital Expenditures. This research hopes that its findings can increase the effectiveness and efficiency of village financial management, especially village funds and capital expenditure to increase village development. Keywords: Village Funds; Capital expenditure; Developing Village Index (IDM)